2019
DOI: 10.3390/nano9091311
|View full text |Cite
|
Sign up to set email alerts
|

Mg Doped CuCrO2 as Efficient Hole Transport Layers for Organic and Perovskite Solar Cells

Abstract: The electrical and optical properties of the hole transport layer (HTL) are critical for organic and halide perovskite solar cell (OSC and PSC, respectively) performance. In this work, we studied the effect of Mg doping on CuCrO2 (CCO) nanoparticles and their performance as HTLs in OSCs and PSCs. CCO and Mg doped CCO (Mg:CCO) nanoparticles were hydrothermally synthesized. The nanoparticles were characterized by various experimental techniques to study the effect of Mg doping on structural, chemical, morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…The increase in PCE is mainly linked to an increase in J sc with , as visible from the J-V characteristic of these devices ( Figure 3 c). A similar trend was observed by Zhang et al [ 32 ] for OSCs with Mg-doped CuCrO 2 thin films as HTL, where an increase of J sc was reported for more conductive films, coherently with our findings. In Zhang’s work, the use of 5%-Mg-doped CuCrO 2 in combination with a non-fullerene AL, PTB7-Th:ITIC, leads to a greater PCE, around 5.2%.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in PCE is mainly linked to an increase in J sc with , as visible from the J-V characteristic of these devices ( Figure 3 c). A similar trend was observed by Zhang et al [ 32 ] for OSCs with Mg-doped CuCrO 2 thin films as HTL, where an increase of J sc was reported for more conductive films, coherently with our findings. In Zhang’s work, the use of 5%-Mg-doped CuCrO 2 in combination with a non-fullerene AL, PTB7-Th:ITIC, leads to a greater PCE, around 5.2%.…”
Section: Resultssupporting
confidence: 93%
“…Based on these considerations, CuCrO 2 was selected as promising HTL in OPV devices. Stoichiometric CuCrO 2 nanoparticles were successfully implemented as HTL in OSC [ 32 ], dye-sensitized solar cells (DSSC) [ 30 ], and perovskite solar cells [ 24 ]. The integration of this nanomaterial in perovskite photovoltaic devices was reported to improve the lifetime of the cells under illumination and the thermal stability of the device [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9] When an emission-selective organic hybrid perovskite solar cells, which yielded a high steady-state PCE of 19.0% versus 17.1% for a typical NiO x -based devices. [38] These studies have indicated that CCO is a very promising HTL for organic photodetector structures, owing to its abundance, favorable band alignment (valence band onset of ≈-5.4 eV) with the donor layer, low electron affinity (≈2.1 eV), high carrier mobility, and small crystal size/roughness. Hsu et al demonstrated CCO as an efficient HTL in non-fullerene acceptor bulk heterojunction organic solar cells (OSCs), to achieving a PCE of 4.97%.…”
Section: Introductionmentioning
confidence: 99%
“…While many publications focus on synthesis and applications of solution-based nanomaterials, issues related to processing, e.g., solvent choice, surface compositions and ligands, particle–particle interaction, and deposition methods, are infrequently addressed. This Special Issue includes nine articles and one review, covering synthesis [1], novel processing [2,3,4,5], and a wide range of applications, such as solar cells [1,3,6], sensors [7], catalysis [8], and electronics [9,10].…”
mentioning
confidence: 99%
“…By applying sulfuric acid to the core-shell nanofibers, the authors showed that the Al 2 O 3 cores were selectively removed while the rest of the original structures were preserved, hence producing CCO hollow nanotubes with an inner diameter of 70 nm and a wall thickness of 30 nm. Zhang et al [6] introduced Mg as a dopant in CCO nanoparticles and examined the effects on the performance of solar cells using these materials as the hole transport layer (HTL). CCO nanoparticles have been shown as an efficient HTL in dye sensitized solar cells [12], organic solar cells [13], and, recently, halide perovskite solar cells [14,15,16,17].…”
mentioning
confidence: 99%